The world, the computer, and the mind: how Andrew Frank helped make human language and cognition cornerstones of geographic information science. Issue 12 (2nd December 2018) - Montello, Daniel R.; Mark, David M.
ABSTRACT: During the late 1980s and early 1990s, cognitive science was included as one of the key disciplines in the emerging multidisciplinary field of geographic information science (GIScience). One of the key proponents and popularizers of the study of human cognition as part of GIScience – and one of its major researchers – has been Andrew U. Frank. In this essay, we review the history of Andrew Frank's role as an innovator and champion for cognitive GIScience, and summarize some of his research contributions in this domain. Taken along with his contributions to other areas of GIScience, this review shows that Andrew Frank has been one of the primary figures in modern GIScience, and among its very broadest and intellectually-diverse contributors.